2014
DOI: 10.1371/journal.pntd.0002655
|View full text |Cite
|
Sign up to set email alerts
|

PCR-Based Techniques for Leprosy Diagnosis: From the Laboratory to the Clinic

Abstract: In leprosy, classic diagnostic tools based on bacillary counts and histopathology have been facing hurdles, especially in distinguishing latent infection from active disease and diagnosing paucibacillary clinical forms. Serological tests and IFN-gamma releasing assays (IGRA) that employ humoral and cellular immune parameters, respectively, are also being used, but recent results indicate that quantitative PCR (qPCR) is a key technique due to its higher sensitivity and specificity. In fact, advances concerning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
85
1
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(108 citation statements)
references
References 91 publications
(92 reference statements)
2
85
1
14
Order By: Relevance
“…The detection percentages of M. leprae DNA can vary from 1 to 10%, likely because of the use of different primers, amplification techniques, and clinical form of the index case Martinez et al, 2014). In our study, no significant association was observed between the bacillary load of the index case and the detection of bacterial DNA.…”
Section: Discussioncontrasting
confidence: 66%
“…The detection percentages of M. leprae DNA can vary from 1 to 10%, likely because of the use of different primers, amplification techniques, and clinical form of the index case Martinez et al, 2014). In our study, no significant association was observed between the bacillary load of the index case and the detection of bacterial DNA.…”
Section: Discussioncontrasting
confidence: 66%
“…Currently, the gold standard for leprosy diagnosis is based on clinical examination and skin biopsy. Techniques based on PCR technology and serological analysis have been developed but were not able to diagnose leprosy with acceptable sensitivity and specificity taking into consideration the different clinical forms and/or bacterial burden (11,(14)(15)(16)(18)(19)(20)(21). Accordingly, identification of biomarkers that allow the diagnosis of leprosy with a greater sensitivity and specificity is still needed.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular techniques using PCR technology and serological tests were developed; however, specificity and sensitivity were limited (11,(14)(15)(16)(17)(18)21). In this context, the identification of biomarkers that allow early diagnosis of leprosy and differentiation between forms of the disease with an adequate sensitivity and specificity is still required.…”
mentioning
confidence: 99%
“…Clinical diagnosis is possible only when the patient is symptomatic, exhibiting skin lesions or presenting the clinical criteria of cardinal signs of leprosy (Martinez et al, 2006). Polymerase chain reaction may be an important tool for helping diagnose leprosy in cases in which clinical findings and SSS are inconclusive, such as with pure neural leprosy, paucibacillary cases, and atypical clinical presentation (Martinez et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Different PCR primers have been used to amplify the DNA of M. leprae from clinical samples (Kang, Kim, Lee, 2003). The PCR targets that are used to detect M. leprae include genes that encode 36 kDa (known as proline-rich antigen [pra] (Parkash et al, 2004;Torres et al, 2003;Hartskeerl, De Wit, Klatser, 1989), 18 kDa (Chae et al, 2002), 85 kDa (Martinez et al, 2014), and 65 kDa (Plikaytis, Gelber, Shinnick, 1990) protein antigens, 16S rRNA (Phetsuksiri, et al, 2006), and repetitive sequences (Donoghue, Holton, Spigelman, 2001). Cox, Kempsell, Fairclough (1991) and Arnoldi et al (1992) detected 8.3 bacilli in skin biopsy samples using primers that amplified a specific sequence that was 172 bp from 16S rRNA.…”
Section: Introductionmentioning
confidence: 99%